Peningkatan Kapasitas Dosen Fisip Unisri Dengan Implementasi Kecerdasan Buatan Untuk Produktivitas Kerja - Sarungu, Lukas; Nugroho, Agung Yudhistira; Wirawan, Riska (Politeknik Indonusa Surakarta, 2025)
he use of artificial intelligence (AI) by university lecturers to support their professional duties remains largely ineffective. There is a need for refresher training programs to reintroduce AI and its applications, particularly for lecturers who rarely or have never utilized AI in fulfilling their responsibilities related to the Tri Dharma of Higher Education. This community service initiative aimed to introduce AI and demonstrate its practical applications to such lecturers. To achieve this goal, an AI training program was developed, focusing on foundational AI concepts and the development of effective prompts. The outcomes of the program indicate a notable improvement in participants' understanding, as evidenced by an increase in post-test scores. The average score rose from 56.5% on the pre-test to 68.3% on the post-test, marking a 20.89% improvement following the AI refresher training provided to FISIP UNISRI lecturers. Keywords: Training; Artificial-intellegence; lecturer; ChatGPT.